Moving “Choreomusically”: Between Theory and Practice - Jordan, Stephanie (Les Cahiers de la Société québécoise de recherche en musique, 2012)
Since the late 20th century, we have witnessed the development of a new interdisciplinary field called ‘choreomusicology’ or ‘choreomusical studies’. In this article, consideration is first given to the histories of the two disciplines music and dance. Their respective lineages are discussed in terms of how each is different, yet how together, they inform the new field. The focus then is on choreomusical analysis, using examples from western theatre dance. Frameworks for analysis are discussed, first, how intermedia research can inform choreomusical theory, then rhythmic strategies, when a flexible concept of parallelism and counterpoint is illustrated through two Stravinsky settings: Pina Bausch’s – Das Frühlingsopfer (Rite of Spring, 1975) and Bronislava Nijinska’s Les Noces (1923). Following discussion of musical embodiment through dance, the theory of conceptual blending is outlined and used in analysis of the Lament from Mark Morris’s setting of Purcell’s Dido and Aeneas (1989).